PERBANDINGAN BIAYA RIIL DENGAN TARIF PAKET INA-CBGâs DAN ANALISIS FAKTOR YANG MEMPENGARUHI BIAYA RIIL PADA PASIEN DIABETES MELITUS RAWAT INAP JAMKESMAS DI RSUP Dr. SARDJITO YOGYAKARTA - , Ratih Pratiwi Sari, dr. I Dewa Putu Pramantara S., SpPD., K-Ger ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The problem usually found in the Jamkesmas (Society Health Insurance) realization is the difference between the real cost and INA-CBGs package tariff for patients using Jamkesmas, especially in inpatient installation. This study was to found out how much the margin was between the real cost and the INA-CBGs package tariff and the factors influence the real cost, and to know the suitability of drug indications in diabetes mellitus inpatiens using Jamkesmas in RSUP (Central General Hospital) Dr. Sardjito Yogyakarta. This study employs analytical observation. The data were taken retrospectively from the Jamkesmas claim files and patientsâ medical record. Subjects were patients with diabetes mellitus type 2 and the research object included the claim files and the medical record of the diabetes mellitus patients using Jamkesmas in RSUP Dr. Sardjito Yogyakarta during period of July 2010 â May 2012 with the diagnosis code INA-CBGs E-4-10-I, E-4-10-II, and E-4-10-III. The data were analyzed descriptively. Besides, one sample test statistical analysis was conducted to find the difference between the real cost and INA-CBGs tariff and the difference between hospital LOS and INA-CBGs package LOS. In addition, to study the relations among the factors that affect the real cost of using bivariate correlation test and regression linier test. The result of the study shows that the different amount between the real cost of the diabetes mellitus patients using Jamkesmas with the severity level I Rp 5.325.126 in 2 episodes of cares